2020
DOI: 10.20411/pai.v5i1.377
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Membrane Protein of SARS-CoV-2 Resembles the Sugar Transporter SemiSWEET

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the disease COVID-19 that has decimated the health and economy of our planet. The virus causes the disease not only in people but also in companion and wild animals. People with diabetes are at risk of the disease. As yet we do not know why the virus has been highly successful in causing the pandemic within 3 months of its first report. The structural proteins of SARS include membrane glycoprotein (M), envelope protein … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 79 publications
3
124
0
Order By: Relevance
“…Coronaviruses, including SARS-CoV-2 that replicate in the cytoplasm compartmentalize their genome transcription in organelle-like structures thereby protecting the virus against host cell defenses and increasing the replication efficiency (Santerre et al 2020). We previously mapped the structural proteins of SARS-CoV-2 and demonstrated that the M protein the virus resembles the sugar transporter SemiSWEET (Thomas, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Coronaviruses, including SARS-CoV-2 that replicate in the cytoplasm compartmentalize their genome transcription in organelle-like structures thereby protecting the virus against host cell defenses and increasing the replication efficiency (Santerre et al 2020). We previously mapped the structural proteins of SARS-CoV-2 and demonstrated that the M protein the virus resembles the sugar transporter SemiSWEET (Thomas, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In silico analysis showed that the M protein of SARS-CoV-2 resembled the prokaryotic sugar transporter SemiSWEET (Thomas, 2020). The nsps are involved in inhibiting host innate immunity, inducing RNA replication and virus exit.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations